2017
DOI: 10.21608/jappmu.2017.46068
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Housing System on Japanese Quail Performance

Abstract: This study was conducted to investigate the effect of two different housing systems; floor pens vs. battery cages on productive traits in Japanese quail. Three hundred, one day old chicks were individually weighed and randomly divided into two equal experimental groups according to housing system (150 birds in each group), each group was randomly assigned to three replicates. Body weight, body weight gain, feed consumption, feed conversion ratio and mortality rates were recorded weekly during the first experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
4
2
0
Order By: Relevance
“…Our findings indicated insignificant difference between FS and CS on livability, and mortality percentages. These results were in accordance with (Badawi, 2017). Economic analysis revealed that, rearing quails on FS had higher Feed cost, TVC, and total cost than those reared on CS.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Our findings indicated insignificant difference between FS and CS on livability, and mortality percentages. These results were in accordance with (Badawi, 2017). Economic analysis revealed that, rearing quails on FS had higher Feed cost, TVC, and total cost than those reared on CS.…”
Section: Discussionsupporting
confidence: 85%
“…The TR and cost of each kg body weight from feed was significantly higher in FS than CS. While NP, GM, BCR, ROI, NP/BW, and NP/BWG were non-significantly higher in CS than FS, this could be due to the non-significance increase in BW in FS than CS, this result was in agreement with (Badawi, 2017), and increasing feed cost in FS than CS, a finding that was in agreement with (Abo Ghanima et al, 2020).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Like chickens, Japanese quails are also related to the Galliformem order and the Phasinidae family (Haqani et al, 2023). The first egg lines were developed by selecting the Japanese quail at the beginning of 1920 when intensive production of the Japanese quail began (Badawi, 2017). Following this, Japanese quails were transported to West Asia, Europe, and America, where extensive research has been conducted on these birds as an avian research model (Minvielle, 2004).…”
Section: Introductionmentioning
confidence: 99%